Malignant tumours of the parotid gland: management of the neck (including the clinically negative neck) and a literature review. Issue 6 (July 2021) - Dell'Aversana Orabona, G.; Salzano, G.; Abbate, V.; Bonavolontà, P.; Committeri, U.; Seidita, F.; Petrocelli, M.; Somma, T.; Improta, G.; Vaira, L.A.; Iaconetta, G.; Califano, L.
Abstract: Major salivary gland malignancies are rare, constituting 1%-3% of head-neck tumours. The surgical management of the clinically negative neck (cN0) does not have a univocal consensus yet. We have carried out a retrospective study on 119 cases of malignant parotid tumours that were surgically treated between January 1999 and January 2014. Our aim was to analyse preoperative findings (cytotype, cTNM) and to correlate these with postoperative results (grading, histotype, occult neck metastasis) in patients with parotid tumours to obtain an appropriate indication for neck management. In cN0 patients with a T1, T2 low-grade cancer a wait-and-see approach is preferred. Instead, in cNO patients with high-grade or low-grade T3, T4 tumours an elective neck dissection (END) is always planned. Levels II, III and IV, at least, must be dissected. The decision to dissect level V or I depends on the location of the primary tumour. In the cN0 group 19 of 58 (32.7%) patients who underwent an END had occult metastases. In clinically positive neck (cN+) patients a Modified Radical Neck Dissection (MRND), at least, must be performed. The criteria to add adjuvant radiotherapy (PORT) include deep lobe parotid tumours, advanced lesions (T3-T4), microscopic (R2) or macroscopic (R1) residual disease after surgery, high grade tumours, perineural diffusion, lymph node metastasis, capsular rupture, and local recurrence after previous surgery. Kaplan-Meier analyses have shown a reduction in the overall survival (OS) from 100% to 91% and in disease-free survival (DFS) from 100% to 95.5% for the NO-PORT and PORT group, respectively. In our study, the cN0 pN+ patients had a higher degree of DFS compared to the cN+.